Identifikasi Sistem Geotermal Mata Air Panas Kampung Mosso Papua Melalui Pemodelan 3D Struktur Bawah Permukaan Menggunakan Metode Gravitasi - Sudrajad, Bangkit; Sutarman, Tatang; Rhofiq, Abdul; Worembai, Andrew; Auparai, Alex Martinus Mamun (Universitas Islam Negeri Alauddin Makassar, 2025)
Geothermal energy presents a promising alternative for electrical power in Indonesia, especially in regions like Papua, where current power plants heavily rely on fossil fuels. As Papua anticipates an increase in energy demand due to regional expansion, exploring renewable energy sources becomes crucial. Mosso Village in the Muara Tami District of Jayapura City is known for its geothermal potential, evidenced by the presence of hot springs in the area. To assess this potential, a geophysical study was conducted focusing on the geothermal system in Mosso Village. This study utilized 3D modeling of subsurface structures through the gravity method. It incorporated both primary and secondary data, with secondary sources including GGMplus gravity model data, digital elevation model (DEM) data, and geological maps. Primary data comprised rock density samples representing surface densities of geological units in the study area. The GGMplus gravity data was central to the analysis, which involved processing, correcting, and modeling these data to identify geothermal features. The 3D modeling revealed a high-density zone at a depth of 1200 m beneath the hot spring source, interpreted as an indication of hot rock or magma intrusion, suggesting it as the geothermal heat source. Additionally, the model identified a low-density area around the hot spring, interpreted as a sedimentary groundwater basin in the geothermal system of Mosso Village. This study highlights the potential for utilizing geothermal energy in the region and provides valuable insights into the geothermal system’s structure.